Identification of Herpes Simplex Virus, Chlamydia Trachomatis, and Mycoplasma Genitalium in Infertile Seminal Fluid Samples Using Multiplex-PCR in Kerman Province, Iran (2016) - Aida Pourmohamadi Siahkali; Kumarss Amini (Mashhad University of Medical Sciences, 2018)
Introduction: Genitourinary tract infections are among the most common causes of infertility in men. These infections could also cause disorders in various parameters, such as the number, motility, viability, and morphology of sperms, as well as the function of the semen, epididymitis, and prostatitis. The present study aimed to determine the prevalence of the bacterial and viral infections associated with the herpes virus, Chlamydia trachomatis, and Mycoplasma genitalium in the seminal fluid of infertile men with unknown cause. Methods: In this descriptive-analytical study, 60 seminal fluid samples were collected from the infertile men referring to an infertility treatment center in Kerman, Iran during May-November 2016. Multiplex-PCR was carried out using specific primers to identify the herpes virus, Chlamydia trachomatis, and Mycoplasma genitalium. Data analysis was performed in SPSS. Results: Out of 60 tested samples, eight cases (13.3%) were positive for the investigated organisms. Among the positive samples, three cases (37.5%) had HSV-1, three samples (37.5%) had C. trachomatis, one case (12.5%) had M. genitalium, and one sample (12.5%) had HSV-2. Conclusion: Findings of the present study regarding the presence of bacterial and viral organisms in the seminal fluid could lay the groundwork for the screening of asymptomatic infections and appropriate treatment before initiating assisted reproductive therapy.